THE IMPLEMENTATION OF GRAMMAR TRANSLATION METHOD IN TEACHING AND LEARNING ENGLISH TO THE STUDENTS OF SMK SARASWATI 3 TABANAN - Sukraningsih, Gusti Ayu Gede; Ni Luh Nanik Puspadi; Ida Ayu Oka Purnami (IKIP SARASWATI TABANAN, 2025)
This research aimed at describing the implementation of Grammar Translation Method in teaching and learning English to the students of SMK Saraswati 3 Tabanan. The subjects of this research were two English teachers and 60 students. The data were collected by utilizing the techniques of observation, interview, and documentation. The data acquired were analysed qualitatively by using qualitative data analysis. The result of this research indicated that: (1) The use of the Grammar Translation Method is still often used, considering the students’ competence was still average in understanding the function of grammar’s rules and vocabulary mastery, particularly in reading and writing; (2) Bilingual teaching is carried out to improve students’ knowledge and skills; and (3)The students are required to be able to translate reading texts correctly and make sentences in correct grammar rather than fluency in language and communication. The conclusion of this research is that the implementation of the Grammar Translation Method is still used in teaching and learning to improve students’ competence in applying the function of grammar rules and vocabulary mastery, particularly in reading and writing. However, Grammar Translation Method prioritizes on applying the function of grammatical rules and improving vocabulary mastery than communication and pronunciation. Therefore, this method is recommended to be adapted by combining with other methods.